Older lesbians' experiences with home care: Varying levels of disclosure and discrimination. Issue 4 (2nd October 2017) - Butler, Sandra S.
ABSTRACT: There is considerable evidence that lesbian, gay, bisexual and transgender (LGBT) older adults have experienced barriers to health care access and have profound fears about how they will be treated in the long-term care system, but the specific experiences of older lesbians have received less attention. Most older adults needing long-term services and supports (LTSS) prefer to remain at home, and this is true for lesbians as well. This article reports on a national, qualitative study of the experiences of 20 older lesbians (age 65 and older) with home care workers. The experiences of six informal partner caregivers with home care services are also included. Emergent themes regarding level of disclosure, experiences with homophobia, evaluation of care received, and thoughts about ideal LTSS are described. Most study participants did not disclose their sexual orientation to their home care workers. A significant minority experienced homophobia, but nearly all ultimately found workers who provided good care with which they were comfortable. Their visions of ideal LTSS included greater affordability and particular qualities that were important for home care workers to possess, such as competence, caring and acceptance. Practice and policy implications are outlined including careful recruitment, training and supervision of home care workers to foster lesbian-sensitive care, but also improved wages and work conditions in order to maintain a quality home care workforce.